Why is Beauty Youtuber so Popular? - Aziezy, Enrico; Pahlevi, Akbar; Suzana, Andhi Johan; P.K., Dian Safitri; Surveyandini, Mayla; Purnomo, Sodik Dwi (International Review of Management and Marketing, 2024)
Due to social isolation and the inability to go outside during the COVID-19 pandemic, social media is vital. Social media influencers on YouTube are popular for brand promotion. However, more research is needed to understand the effectiveness of social media influencer marketing and message appeal campaigns. This study uses 800 YouTube videos observed directly to determine social media influencer marketing’s performance via customer engagement. According to the study, informational and emotional message appeals affect Instagram customer engagement differently, while sponsorship and expertise moderate the effect. In customer involvement, informational message appeals work better than emotional ones. Sponsorship disclosures improve client engagement in informational videos. In addition, informational message appeals attract customers better than emotional appeals when knowledge is high. The study shows that message appeals, sponsorship, and expertise can engage customers.